Pathogenesis and Minimally Invasive Management of Subcutaneous Emphysema: A Narrative Literature Review - Syafitra, Said Tryanda; Sri Indah Indriani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Subcutaneous emphysema is the result of air infiltrating the subcutaneous and soft tissues. The prevalence of subcutaneous emphysema varies between 0.43% and 2.34%. Subcutaneous emphysema typically results in mild symptoms, poses no significant risk, and does not necessitate specific medical intervention. Pathologies affecting underlying tissues can exhibit greater severity and pose a risk to life. Subcutaneous emphysema is a challenge in terms of how to handle it. The treatment should initiate a focused endeavor to determine the underlying etiology of subcutaneous air dissection. This literature review focuses on subcutaneous emphysema, specifically exploring its pathogenesis and therapy strategies for people with this condition.